La participación que tienen los niños y niñas desde el curriculum vivido - Quezada Ramírez, Catalina Andrea (2023)
This research contributes to the curricular study in early childhood from a participatory perspective, understanding that its development in each context is unique and particular, for this reason, it sought to know the discourses of Second Level School Transition boys and girls about their participation in the Living Curriculum. The research was approached from a comprehensive qualitative approach and a phenomenological design. Individual interviews with educators and group interviews with boys and girls were conducted, the latter using the photo-elicitation technique. Among the main results, they highlight that, from the perspective of boys and girls, a simple participation in Educational Establishments would be developed, evidencing that they would not be an active part of the construction of their teaching and learning processes. In relation to the results of the educators, it is evident that they have carried out experiences that point to a more passive participation, however, since their speeches can show that their participatory practices correspond to conceptualized and democratic experiences. From a contrast of the discourses, it can be deduced that there would be a more "real" participation outside the classroom and that both discourses are assimilated in reflection of the same experience of prescription from school.